2020
DOI: 10.7150/thno.45845
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin receptor in B cells plays a role in bone remodeling in mice

Abstract: Erythropoietin (EPO) is a key regulator of erythropoiesis. However, EPO receptors (EPO-Rs) are also expressed on non-erythroid cell types, including myeloid and bone cells. Immune cells also participate in bone homeostasis. B cells produce receptor activator of nuclear factor kappa-Β ligand (RANKL) and osteoprotegerin (OPG), two pivotal regulators of bone metabolism. Here we explored the ability of B cells to transdifferentiate into functional osteoclasts and examined the role of EPO in this process in a murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…This finding is in line with the lower expression of RANKL ( Figure 5B). We also found a lower frequency of B-cell-derived preosteoclasts (Figures 6B,C), defined as CD115 + /β3 integrin + Pro-B cells (23), which correlates with lower osteoclastogenic potential observed following B cell depletion ( Figure 6A).…”
Section: Anti-cd20-mediated B Cell Depletion Decreases the Frequency supporting
confidence: 65%
See 2 more Smart Citations
“…This finding is in line with the lower expression of RANKL ( Figure 5B). We also found a lower frequency of B-cell-derived preosteoclasts (Figures 6B,C), defined as CD115 + /β3 integrin + Pro-B cells (23), which correlates with lower osteoclastogenic potential observed following B cell depletion ( Figure 6A).…”
Section: Anti-cd20-mediated B Cell Depletion Decreases the Frequency supporting
confidence: 65%
“…B cells were shown to undergo trans-differentiation to macrophages (22) and these cells share similarities with osteoclast precursors (22). In this context, we have recently demonstrated B-cell-derived osteoclastogenesis both in vitro and in vivo (23). Notably, our data indicate that among BM B cells, only Pro-B cells bearing the receptor for macrophage colony-stimulating factor (MCSF-R, also known as cFms or CD115), are capable of giving rise to functional osteoclasts (23).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Deshet-Unger and colleagues probed the hypothesis that osteoclasts also arise from bone marrow B cells. 22 They found that EPO enhances the ability of B cells to transdifferentiate into functional osteoclasts by upregulating the expression of known osteoclastogenic molecules such as RANKL. 22,32,33 They investigated B cell-derived osteoclastogenesis using histologi- To explore the impact of Epo-Epor signaling in B cells on bone loss, they utilized mice with conditional Epor knock-down (cKD) in the B cell lineage.…”
Section: Effect Of Epo On Bone Marrow B-cellsmentioning
confidence: 99%
“…22 They found that EPO enhances the ability of B cells to transdifferentiate into functional osteoclasts by upregulating the expression of known osteoclastogenic molecules such as RANKL. 22,32,33 They investigated B cell-derived osteoclastogenesis using histologi- To explore the impact of Epo-Epor signaling in B cells on bone loss, they utilized mice with conditional Epor knock-down (cKD) in the B cell lineage. 34 Analysis of these cKD femurs by microcomputed tomography revealed an increased cortical and trabecular bone mass when compared with control mice.…”
Section: Effect Of Epo On Bone Marrow B-cellsmentioning
confidence: 99%